IMPLEMENTATION OF INTERSUBJECT CONNECTIONS IN THE SPHERE OF ENVIRONMENTAL EDUCATION - Озерова, Л.А.; Сажієнко, А.П. (Modern engineering and innovative technologies, 2023)
The article analyzes the content of environmental education in modern conditions. The principles of environmental education and the components of the interdisciplinary composition of the content of environmental education are determined. The functions and